Implementasi Metode K-Nearest Neighbor pada Purwarupa Jemuran Otomatis berdasarkan Sensor Hujan dan Intensitas Cahaya - Pabela Purwa Wiyoga; Rizal Maulana; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Indonesia, which has a tropical climate, gets sunshine all year round. It is very useful for people to dry household or industrial needs. Examples of industries that use sunlight are the production of crackers, salted fish, coffee, and unhulled rice and others. However, apart from getting the continuous heat of the sun, there is also rain that is present erratically. So leaving things outdoors will be risky, especially during the rainy season. Therefore, the researchers created a sun dry system that can be put outside automatically when the outdoor conditions are sunny and there is no rain, and inserted when the outdoor conditions are rainy or there is no sunlight. These conditions will be taken using a raindrop sensor and a light dependent resistor sensor. Arduino Nano as a microcontroller used to control sensors and actuators. To control the system using the K-Nearest Neighbors method. After testing, obtained good results. The best value of accuracy and computation time in using the K-Nearest Neighbors method is at k=3 with the average accuracy of 98% and the computation time is 37.173 microseconds. When compared with the if-else method, the if-else method has an accuracy value of 100% and a computation time of 13.232 microseconds. The K-Nearest Neighbor method is feasible to implement in this system, but a simple if-else method is more profitable due to better accuracy and simpler source code.